2018
DOI: 10.1183/13993003.01787-2018
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of resting haemodynamics in chronic thromboembolic disease without pulmonary hypertension

Abstract: There is renewed interest in the haemodynamic definitions of pulmonary hypertension (PH), reigniting an old debate about diagnostic thresholds [1]. Recent prospective data support work dating back over 40 years demonstrating patients with "borderline" PH (mean pulmonary artery pressure (mPAP) <25 mmHg) can still have significant morbidity and mortality [2]. Therefore, lowering the mPAP threshold for the diagnosis of precapillary pulmonary arterial hypertension (PAH) has been discussed at World Symposium on Pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…However, it remains unclear to what extent PH and [31,54,55]. Patients with chronic thrombo-embolic pulmonary disease (CTEPD) without PH still represent a small proportion of the patients referred to CTEPH centres [56].…”
Section: Group 2 Pulmonary Hypertension Associated With Left Heart Di...mentioning
confidence: 99%
“…However, it remains unclear to what extent PH and [31,54,55]. Patients with chronic thrombo-embolic pulmonary disease (CTEPD) without PH still represent a small proportion of the patients referred to CTEPH centres [56].…”
Section: Group 2 Pulmonary Hypertension Associated With Left Heart Di...mentioning
confidence: 99%
“…In contrast, for patients with PH due to left heart disease or lung disease (Groups 2 and 3, respectively), such studies cannot be performed as there are currently no recommended treatment options available for these conditions 2 , 3 . For patients with Group 4 PH [chronic thromboembolic PH (CTEPH)], the lower mPAP threshold in the revised definition may lead to some patients who are classified based on the previous definition as having chronic thromboembolic disease without PH (CTED) being reclassified as having CTEPH 26 , 27 . As pulmonary endarterectomy—the gold-standard treatment recommended for operable CTEPH 2 , 3 —is also a beneficial treatment for operable CTED patients, 27 , 28 the revised definition is not expected to change the management of these patients.…”
Section: The Impact Of the Revised Definition Of Pulmonary Hypertensimentioning
confidence: 99%
“…28 A prospective study of 34 patients with CTED in the UK reported that up to 56% had mPAP ≤ 20 mmHg. 29 BPA has been performed in small numbers of patients with CTED. Preliminary data have shown improvements in functional parameters and hemodynamics after BPA in patients with symptomatic CTED, [30][31][32] although larger prospective studies are required to further investigate these findings.…”
Section: Bpa For Chronic Thromboembolic Disease Without Pulmonary Hypmentioning
confidence: 99%